APLIKASI KELAS ONLINE JURUSAN TEKNIK INFORMATIKA FAKULTAS TEKNIK UNIVERSITAS PALANGKA RAYA - Nova Noor Kamala Sari; Deddy Ronaldo (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2018)
The designed online class is used to provide additional values to the learning process in theDepartment of Informatics Engineering of University of Palangka Raya. It basically does notreplace the entire learning process because the learning process is thus far implemented in theclassroom. Yet,the application of online classroom provides extra features, such as creating writtenmaterials directly on the web and uploading the materials in PDF or PPT which then can beobtained directly by students on the web. Students can upload their given assignments on the web aswell; therefore the lecturers no longer need to bring a stack of printed reports or papers of thestudent assignments.Modeling application of online class in this research aims at applying UML-based WebEngineering method (UWE) apart from waterfall engineering method which is often taught to thestudents of Department of Informatics Engineering of University of Palangka Raya.The result of this research shows that the website program on online class can be implementedby the lecturers and students majoring in Informatics Engineering by applying model application ofUML-based Web Engineering method (UWE).